Evidence on the Determinants of Inventory Accounting Policy Choice - Cushing, Barry E.; LeClere, Marc J. (The Accounting Review, 1992)
[This study provides additional evidence on factors influencing inventory accounting policy choice. Following Lee and Hsieh (1985), Dopuch and Pincus (1988), and Lindahl (1989), we compare long-time FIFO users with long-time LIFO users to test variables that might be expected to influence inventory method choice. This study incorporates a tax savings variable in evaluating the LIFO/FIFO choice. We also survey financial executives to corroborate the results of secondary data analyses and to seek new insights about inventory method choice. The findings suggest that: (1) anticipated tax savings is the primary reason firms use LIFO and (2) other firms do not use LIFO because of numerous factors without a single dominant reason. Most of these factors diminish the potential tax savings from LIFO. They include LIFO layer liquidations, LIFO bookkeeping costs, declining production costs, and contradictory tax and financial reporting rules on accounting for inventory obsolescence. However, other factors include effects on debt covenants, concern about the complexity of LIFO, and the requirements of FIFO for government contracts. Two unexpected findings emerged. First, the multivariate model is quite accurate in predicting FIFO firms, but predicts less then half of those using LIFO. Second, the correspondence between the responses to the FIFO survey and the cross-sectional data is not as strong as might be expected, which suggests that determinants of inventory choice continue to be elusive.]